“ГУТАЛ” ХЭМЭЭХ ҮГИЙН ХЭЛ, СОЁЛЫН АСУУДАЛД - Д.Баасанбат (Acta Mongolica, 2013)
This article mentioned that about the boots worlds culture, including Mongolian boots culture such as wearing, origin words and phrases about boots, in oral and literature. The writer claritied in his article that Mongol boots names and Mongolian minority special features, fashion, forms, and usages.